The Prognostic Value of NANO Scale Assessment in IDH-Wild-Type Glioblastoma Patients - Kasper, Johannes; Wende, Tim; Fehrenbach, Michael Karl; Wilhelmy, Florian; Jähne, Katja; Frydrychowicz, Clara; Prasse, Gordian; Meixensberger, Jürgen; Arlt, Felix (Frontiers in Oncology, 2021)
Background IDH-wildtype glioblastoma (GBM) is the most frequent brain-derived malignancy. Despite intense research efforts, it is still associated with a very poor prognosis. Several parameters were identified as prognostic, including general physical performance. In neuro-oncology (NO), special emphasis is put on focal deficits and cognitive (dys-)function. The NANO scale was proposed in order to standardize assessment of neurological performance in NO. This study evaluated whether NANO scale assessment provides prognostic information in a standardized collective of GBM patients. Methods The records of all GBM patients treated between 2014 and 2019 at our facility were retrospectively screened. Inclusion criteria were age over 18 years, at least three months follow-up, pre-operative and post-operative cranial magnetic resonance imaging. NANO scale was assessed pre- and post-operatively as well as at three months follow-up. Univariate and multivariate survival analyses were carried to investigate prognostic value. Results 131 patients were included. In univariate analysis, poor post-operative neurological performance (HR 1.13, p=0.004), poor neurological performance at three months follow-up (HR 1.37) and neurological deterioration during follow-up (HR 1.38, both p<0.001), all assessed via NANO scale, were associated with shorter survival. In multivariate analysis including other prognostic factors such as extent of resection, adjuvant treatment regimen or age, NANO scale assessment at three months follow-up was independently associated with survival prediction (HR 1.36, p<0.001). The optimal NANO scale cutoff for patient stratification was 3.5 points. Conclusion Neurological performance assessment employing NANO scale might provide prognostic information in patients suffering from GBM.